Potency of the Common Intercultural Perspectives about Community and Individuality - Melville, Gert (Walter de Gruyter GmbH, 2016)
How have different civilizations throughout different epochs mastered fundamental challenges of life? The series analyses the basic questions of cultural anthropology. All epochs and the most significant civilizations worldwide, as well as different epistemological aspects including historical sciences, sociology, ethnology, art, literature and philosophy are brought together
Description based on publisher supplied metadata and other sources
Keywords: Corporate culture; Ethnische Gruppe; Individualität; Gemeinschaft; Kulturelle Identität; Südamerika